NASA 36.356 Rocket Profile of Nitric Oxide in the Polar Night - Bailey, Scott; Thurairajah, Brentha (University Libraries, Virginia Tech, 2022)
The associated date file contains retrieved nitric oxide volume and column densities in the mesosphere and lower thermosphere as a function of altitude. The observations were made under polar night conditions.